Rice Husk Silica-Based magMCM-41 Composites: Synthesis, Characterization, and Pb(II) Adsorption Performance - Nita Trisnawati; Eti Rohaeti; Deden Saprudin; Sarah Yasir (Program Studi Kimia Universitas Negeri Jakarta, 2026)
Lead (Pb) contamination in water poses serious environmental and health risks, necessitating the development of effective and sustainable adsorbents for its removal. This study aimed to synthesize and characterize magMCM-41 composites derived from rice husk silica, and evaluate their performance for Pb(II) ion removal in aqueous solutions. The magMCM-41 was prepared by integrating magnetite (Fe3O4) nanoparticles into a mesoporous silica framework via co-preparation and sol-gel methods using cetyltrimethylammonium bromide (CTAB) as a template. Characterization by XRD, FTIR, BET, and PSA confirmed successful composite formation, revealing a high specific surface area o f 476.744 m2/g, a mesoporous framework (pore diameter 3.83 nm), and an average particle size of 362.7 nm. Adsorption conditions were optimized using Response Surface Methodology (RSM); pH positively influenced capacity, whereas adsorbent dosage had a negative effect. The maximum adsorption capacity was 115.77 mg/g at pH 5 with 0.05 g of adsorbent. The Dubinin-Radushkevich model best described the adsorption equilibrium (R2=0.935), indicating physisorption on a heterogeneous surface. Thermodynamic analysis confirmed a spontaneous and exothermic process. These results demonstrate that rice husk-derived magMCM-41 is a sustainable and magnetically separable adsorbent with high potential for Pb(II) remediation.